ЛИНГВОКОГНИТИВНЫЙ подход К ИЗУЧЕНИЮ РЕГИОНАЛЬНОЙ ОНОМАСТИКИ - ЩЕРБАК, АНТОНИНА (Studia Rossica Posnaniensia, 2006)
The author analyses the part of Tambov Region onomasticon - that is personal nickname-like proper names. Onomasiological types of nicknames, reason for their emergence, their connection to specific social groups and gender have been presented in the paper against the background of conceptual and linguistic picture o f the world.